2022
DOI: 10.1002/adma.202105821
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Foams via Frontal Polymerization

Abstract: The properties of foams, an important class of cellular solids, are most sensitive to the volume fraction and openness of its elementary compartments; size, shape, orientation, and the interconnectedness of the cells are other important design attributes. Control of these morphological traits would allow the tailored fabrication of useful materials including highly porous solids, anisotropic heat conductors, tough composites, among others. While approaches like ice templating has produced foams with elongated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 24 publications
6
34
0
Order By: Relevance
“…Recently, the introduction of various metal NPs and lipase enabled the realization of distinctive foam morphologies and functionalities 36 . Similar phenomena were observed from FROMP-mediated foams by embedding secondary solvent 24 and polymeric microparticles 21 in the monomer layer. While different combinations of monomer-secondary phase systems still remain widely unexplored in DCPD FROMP, we were inspired to examine how the intrinsic morphology of rigid rod-like CNCs would affect the construction of the pDCPD monolith microstructure in situ.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Recently, the introduction of various metal NPs and lipase enabled the realization of distinctive foam morphologies and functionalities 36 . Similar phenomena were observed from FROMP-mediated foams by embedding secondary solvent 24 and polymeric microparticles 21 in the monomer layer. While different combinations of monomer-secondary phase systems still remain widely unexplored in DCPD FROMP, we were inspired to examine how the intrinsic morphology of rigid rod-like CNCs would affect the construction of the pDCPD monolith microstructure in situ.…”
Section: Resultssupporting
confidence: 74%
“…For example, M. Garg et al 23 recently reported a production of porous or vascularized DCPD monolith via a synchronized ring-opening metathesis polymerization (ROMP) and depolymerization of DCPD and a poly(propylene carbonate) sacrificial layer, respectively. Moreover, D. M. Alzate-Sanchez et al 24 studied the relationship between blowing agents, gelation time, and resin viscosity in the production of anisotropic channels within DCPD foams. Despite these cutting-edge results, a more homogeneous pore organization may be achieved by reducing the dependency of foam porosity to the number of sacrificial layers and the long delay time derived from precursor formulations.…”
Section: Introductionmentioning
confidence: 99%
“…In FROMP, Grubbs-type Ru catalysts rapidly transform liquid or gel-state resins of dicylopentadiene ( DCPD ) into thermoset materials. After an initial thermal , or photo , trigger, the heat generated by ring-opening drives subsequent catalytic events in advance of the reaction zone. The resultant polymerization front traverses through the monomer resin with a well-defined monomer to polymer interface at a steady-state velocity (ν f ).…”
mentioning
confidence: 99%
“…Our group recently leveraged blowing agents (solvents) for the generation of foams from FROMP of DCPD. 22 Rather than the addition of blowing agents, we envisioned using the inherent generation of nitrogen from the radical initiator as well as the boiling of monomer to generate voids in the propagating polymer front. Using tandem FRaP and FROMP upward, in situ mixing of the two layers would form gradient foams through bubble formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As the gas bubbles form, they are trapped by the propagating front to create a foam. Our group recently leveraged blowing agents (solvents) for the generation of foams from FROMP of DCPD . Rather than the addition of blowing agents, we envisioned using the inherent generation of nitrogen from the radical initiator as well as the boiling of monomer to generate voids in the propagating polymer front.…”
Section: Resultsmentioning
confidence: 99%